Hubungan Pola Asuh Autoritatif Dan Kecerdasan Intelektual Dengan Self-Regulated Learning Pada Siswa Sekolah Menengah Atas - Ronal Hasudungan Gultom; Nefi Darmayanti; Hasanuddin Hasanuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between authoritative parenting and intellectual intelligence with self-regulated learning in students of SMA Muhammadiyah 2 Medan. The population is 562 students and the sampling technique is using purposive sampling technique. the research sample is 115 students. The measuring instrument used is the authoritative parenting scale, the intellectual intelligence test, namely the SPM and the self-regulated learning scale. Data analysis technique in this research is using multiple regression analysis technique. The results showed that there was a significant relationship between authoritative parenting and self-regulated learning. This is evidenced by the correlation coefficient (rx1y) of = 0.574 with p = 0.000 < 0.050, thus it can be concluded that the better the authoritative parenting pattern, the better the self-regulated learning. There is a significant relationship between intellectual intelligence and self-regulated learning. This is indicated by the correlation coefficient of (rx2y) = 0.818 with p = 0.001 < 0.050, thus it can be concluded that the better intellectual intelligence, the better self-regulated learning. There is a significant relationship between authoritative parenting and intellectual intelligence with self-regulated learning in students. This is evidenced by the correlation coefficient (rx1x2y) = 0.843 p = 0.000 < 0.050, thus it can be concluded that authoritative parenting and intellectual intelligence together affect self-regulated learning. Furthermore, seen from the value of the determinant coefficient (R2) of authoritative parenting and intellectual intelligence with self-regulated learning is equal to = 0.771 this shows that authoritative parenting and intellectual intelligence contribute effectively or contribute to self-regulated learning by 77.1%. Therefore, there is still a contribution of 28.9% of the influence of other factors that can be investigated by further researchers.